The Views of Provincial School Inspectors on the Obstacles to Communication with Teachers in the Counseling and Inspection Process - Gokyer, Necmi (Elsevier Science Bv, 2015)
study aims to identify the views of provincial school inspectors on the obstacles to communication with teachers during the counseling and inspection process. The study uses the survey model, and its population comprises a total of 340 provincial school inspectors. Of these, 151 were based in 6 of the 12 Eastern Anatolian provinces selected by taking into account the number of school inspectors in these provinces (Agri, Bingol, Elazig, Erzurum, Malatya and Van). The remaining 189 were based in 4 of the 8 Southeastern Anatolian provinces selected once again by considering the number of school inspectors in these provinces (Diyarbakir, Gaziantep, Siirt and Sanliurfa). A total of 279 data collection instruments were returned and evaluated. (C) 2015 The Authors. Published by Elsevier Ltd.
3rd World Conference on Psychology and Sociology -- NOV 06-08, 2014 -- TURKEY
Keywords: primary school; secondary school; communication; counseling; inspection; provincial school inspector